Hyperuricemia and Associated Cardiometabolic Factors: A Cross-sectional Study on Taxi-motorbike Drivers Working in Cotonou, Benin - AVOGBE, PATRICE HODONOU; SANNI, AMBALIOU (My University, 2022)
Background: An elevated level of uric acid (UA), also known as hyperuricemia (HUA), contributes to the occurrence of cardiovascular diseases (CVDs). However, epidemiolocal features of HUA in populations of Benin are rare. Objectives: We identified clinical and metabolic factors associated with HUA in taxi-motorbike drivers (TMDs) of Cotonou. Methods: A total of 134 participants with a mean age of 39.3 years were analyzed using a retrospective cross-sectional study design. Data from a self-administered questionnaire and biochemical markers including, plasma UA, glucose, insulin, creatinine, and lipids were obtained from each participant. HUA was defined as plasma UA greater than 416 μmol/L. Insulin resistance (IR) was determined using the homeostatic model assessment (HOMA). Logistic regression analysis was performed to determine the association of various risk factors with HUA. Odds ratio (OR) and 95% confidence interval (CI) were calculated for HUA. Results: The overall prevalence of HUA was 19.4% (95% CI: 12.7-26.1) in TMDs. Multivariable logistic regression showed that IR (OR = 3.60, 95% CI: 1.27-10.22, P = 0.02), hypertension (OR = 2.75, 95% CI: 1.00- 7.54, P=0.05), and triglycerides (TG; OR=4.25, 95% CI: 1.39-12.98, P=0.01) were risk factors for HUA. Furthermore, creatinine was inversely associated with HUA (OR=0.62, 95% CI: 0.41-0.94, P=0.02). Conclusion: HUA was found in 19.4% of the patients. In addition, hypertension, IR, creatinine, and TG levels were independently associated with HUA in TMDs. Therefore, the monitoring of these markers may help prevent HUA.
Keywords: Cotonou; Hypertension; Hyperuricemia; Insulin resistance; Taxi-motorbike drivers; Uric acid